Mappe-Monde en deux hémisphères. - Legay (Impie. Legay, 1860)
Map shows six continents and partial coast for "Océan Glacial Antarctique"; Western Hemisphere on right-hand side. Map is from Atlas Delamarche. Inset: Passage du Nord-Ouest [Northwest Passage]. Relief shown by hachures. Scale not given.